Comparative Transcriptome Reveals the Molecular Regulation Mechanism of Charybdis japonica to High- and Low-Temperature Stresses - Lou, Fangrui; Wang, Yuju; Han, Zhiqiang; Shui, Bonian (Frontiers in Marine Science, 2022)
Intertidal organisms are more sensitive to temperature stresses (whether high or low temperatures). As an intertidal crustacean, the optimal survival temperature ranges of Charybdis japonica are from 20 to 27 °C. In this study, C. japonica was selected as the research species to better explore the molecular regulatory mechanisms of intertidal crustaceans to temperature stresses. The transcriptomes of C. japonica exposed to three temperature gradients (12, 20, and 28 °C) were sequenced. A total of 69.22 Gb clean transcriptome reads were obtained from nine libraries and then de novo assembled to 52,972 unigenes with a mean length of 1080.23 bp and an N50 length of 1,775 bp. A total of 20,121 unigenes were successfully matched with at least one protein database. The transcriptome structure was predicted, and 12,125 coding sequences and 12,854 simple sequence repeats were obtained. The gene expression level of C. japonica at 20 °C was used as control, and 548 and 90 unigenes were significantly differentially expressed at 28 and 12 °C, respectively. A total of 720 unigenes were significantly differentially expressed at 28 °C compared with 12 °C. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes annotation showed that genes related to cell structure, metabolism, and protein folding and hormone synthesis might be involved in the regulation of temperature stress in C. japonica. Our results reveal for the first time the response of C. japonicas to low- and high- temperature stresses at the transcriptome level. The results provide fundamental information for revealing the temperature regulation mechanisms of C. japonica and other intertidal crustaceans. Furthermore, the present study enhances our understanding of how temperature fluctuations will affect the survival of marine crustaceans.